Project Selection for Construction Businesses in Indonesia Using AHP: A Case of CV. Maezurra Indotama - Maharani, Shafa Dwidiva; Siallagan, Manahan Parlindungan Saragih (PT. EQUATOR SINAR AKADEMIA, 2024)
The construction industry is the backbone of Indonesia's economy but needs operational inefficiencies like slow payment processes and a complicated bureaucratic structure. The research applies AHP to analyze the project selection criteria of small firms in the particular case of CV. Maezurra Indotama. Key decision criteria were identified through expert interviews and pairwise comparisons contract management, fund security, and schedule management. The findings indicate the high importance of contract review periods at 42.2%, client's fund availability at 47.0 %, and payment scheduling at 29.1%. The School Renovation Project came out as the most preferred option, aligned with the strategic focus. Suggestions and the way forward include enhancement of contract management through standard templates, preparation of adequate funds, and setting reasonable timelines. With these attributes in place, competitive growth of the construction sector will be achieved.